Author Correction: Two-qubit sweet spots for capacitively coupled exchange-only spin qubits (npj Quantum Information, (2021), 7, 1, (112), 10.1038/s41534-021-00449-4) - Feng, MengKe (Nature Research, 2022)
10.1038/s41534-021-00475-2